(Un-)Sustinability of public finances in German Laender: A panel time series approach - Heiko T. Burret; Lars P. Feld; Ekkehard A. Köhler (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2015)
This paper provides evidence that most German states (Laender) have unsustainable public finances by exploiting a newly compiled database covering the years 1950-2011. Although the Laender are closely intertwined we are the first to apply 'second generation' panel techniques that control for correlation among the Laender. A unique identification strategy for the selection of relevant sub-panels improves the robustness of the tests.
Keywords: E62; H62; H77; H72; 330; Fiscal Sustainability; Federalism; Panel Cointegration; Cross Dependence